2021
DOI: 10.1227/neu.0000000000001737
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Donor Nerve to Restore Elbow Flexion After Traumatic Brachial Plexus Injury: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND:Traumatic brachial plexus injuries (BPIs) often lead to devastating upper extremity deficits. Treatment frequently prioritizes restoring elbow flexion through transfer of various donor nerves; however, no consensus identifies optimal donor nerve sources.OBJECTIVE:To complete a meta-analysis to assess donor nerves for restoring elbow flexion after partial and total BPI (TBPI).METHODS:Original English language articles on nerve transfers to restore elbow flexion after BPI were included. Using a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In his study, 91% (10 of 11) patients who underwent intercostal-to-musculocutaneous nerve transfer achieved more than M3 elbow flexion power. Similarly, in a recent systematic review, 77.7% (539 of 703) of patients who underwent intercostal-to-musculocutaneous achieved more than M3 elbow flexion power [ 8 ]. When compared to this systematic review, Ochiai’s report showed excellent results.…”
Section: Introductionmentioning
confidence: 99%
“…In his study, 91% (10 of 11) patients who underwent intercostal-to-musculocutaneous nerve transfer achieved more than M3 elbow flexion power. Similarly, in a recent systematic review, 77.7% (539 of 703) of patients who underwent intercostal-to-musculocutaneous achieved more than M3 elbow flexion power [ 8 ]. When compared to this systematic review, Ochiai’s report showed excellent results.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, in case of extensive nerve gaps or severe pelvic adhesion, when directly coaptation or nerve graft is impossible, nerve transfer has been reported to be a simple and valid therapeutic option, especially in upper limb nerve injuries. [6][7][8][9][10] Concerning femoral nerve lesions, the obturator nerve has been recommended as an ideal donor nerve by several pieces of literature recently for nerve transfer. Campbell et al 11 first described intropelvic obturator nerve transfer to the femoral nerve in a patient with a 15-cm nerve gap caused by resection of retroperitoneal Schwannoma and reported good outcomes with a nearly normal gait and grade 4 strength of the quadriceps 2 years postoperatively.…”
mentioning
confidence: 99%
“…Direct nerve repair or nerve grafting is still the criterion standard treatment for peripheral nerve injuries 5 . However, in case of extensive nerve gaps or severe pelvic adhesion, when directly coaptation or nerve graft is impossible, nerve transfer has been reported to be a simple and valid therapeutic option, especially in upper limb nerve injuries 6–10 …”
mentioning
confidence: 99%